686 Preclinical characterization of a novel therapeutic antibody targeting LILRB2. (10th December 2020) - Costa, Maria Jose; Stafford, Ryan; Ku, Zhiqiang; Ma, Jing-Tyan; McCutcheon, Krista; Liu, Xiaoye; Chen, Heyu; Hong, Kyu; Huang, Tao; Zhang, Ningyan; An, Zhiqiang; Zhang, Cheng Cheng; et al.
Abstract : Background: Myeloid-derived suppressor cells and tumor-associated macrophages inhibit anti-cancer immune responses systemically and in the tumor microenvironment, respectively, thereby limiting the efficacy of immune checkpoint blockers. 1–5 However, the plasticity of myeloid cells may enable therapeutic intervention. The inhibitory receptor LILRB2/ILT4, which is expressed primarily in myeloid cells (monocytes, macrophages, dendritic cells and neutrophils), has emerged as a key immune checkpoint mediating the tolerogenic activity of myeloid cells associated with cancer. 6–8 LILRB2/ILT4 has several ligands (classical and non-classical MHC-I, ANGPTL2/5, SEMA4A and CD1) and most of these are known to contribute to immune suppression in the tumor microenvironment. 9–14 Thus, LILRB2/ILT4 is a promising target to overcome protumor myeloid cell activity. IO-108 is a fully human IgG4 therapeutic candidate that binds LILRB2/ILT4 with high affinity and specificity, thereby blocking its ligand interactions. Methods: We used computational approaches to evaluate LILRB2/ILT4 expression in solid tumors from TCGA. IO-108 was discovered from a phage-displayed human single chain variable fragment antibody library. IO-108 contains the S228P mutation in the hinge region to prevent Fab-arm exchange. The binding affinity of IO-108 was measured using biolayer interferometry. The specificity of IO-108 was confirmed by two methods: 1) ELISA using recombinant LILR family members; 2) flow cytometry using cell lines engineered to express the extracellular domain of every LILR on the cell surface. Reporter and ligand binding assays were used to demonstrate LILRB2/ILT4 blocking activity of IO-108. Functional studies using primary immune cells from healthy donors and solid tumor cancer patients were performed to characterize IO-108 activity and mechanism of action. The in vivo efficacy of IO-108 is currently being evaluated in mouse models. Results: We found high LILRB2/ILT4 expression associated with macrophage infiltration in many solid tumor types from TCGA. IO-108 binds to LILRB2 with high affinity and specificity and blocks LILRB2/ILT4 ligand binding and activation. IO-108 enhanced the production of multiple proinflammatory cytokines in LPS- and anti-CD3- stimulated PBMC cultures from healthy donors and potentiated DC maturation/activation in response to LPS. Moreover, IO-108 polarized primary CD14+ cells isolated from solid tumor patient PBMC and ovarian cancer-associated ascites towards a proinflammatory phenotype and attenuated their suppressive effect on autologous T-cell proliferation and production of tumoricidal cytokines. Conclusions: The preclinical characterization of IO-108, a novel LILRB2/ILT4 antagonistic antibody, demonstrates its ability to polarize tumor-associated myeloid cells towards a proinflammatory phenotype and suggests potential therapeutic benefit in tumors unresponsive to immune checkpoint blockade. Acknowledgements: We acknowledge the funding support from National Cancer Institute (1R01 CA248736 and 2P30 CA142543), the Welch Foundation (AU-0042-20030616) and the Cancer Prevention and Research Institute of Texas (RP150551 and RP190561). Ethics Approval: PBMCs were isolated from buffy coats of healthy donors (Interstate Blood Bank). Hematopoietic samples from cancer patients were obtained through the services of the Simmons Cancer Center's Tissue Management Shared Resource with IRB approved protocol (STU 102010-051). All animal work was approved and conducted under the oversight of the UT Southwestern Institutional Animal Care and Use Committee (IACUC). References: Hanahan D, Coussens LM. Accessories to the crime: functions of cells recruited to the tumor microenvironment. Cancer Cell 2012;21 :309–22. Galluzzi L, Chan TA, Kroemer G, et al. The hallmarks of successful anticancer immunotherapy. Sci Transl Med 2018;10, DOI: 10.1126/scitranslmed.aat7807.3. Talmadge JE, Gabrilovich DI. History of myeloid-derived suppressor cells. Nat Rev Cancer 2013;13 :739–52. Mantovani A, Marchesi F, Malesci A, et al. Tumour-associated macrophages as treatment targets in oncology. Nat Rev Clin Oncol 2017;14 :399–416. Cassetta L, Pollard JW. Targeting macrophages: therapeutic approaches in cancer. Nat Rev Drug Discov 2018;17 :887–904. Chen H-M, van der Touw W, Wang YS, et al. Blocking immunoinhibitory receptor LILRB2 reprograms tumor-associated myeloid cells and promotes antitumor immunity. J Clin Invest 2018;128 :5647–62. Chang CC, Ciubotariu R, Manavalan JS, et al. Tolerization of dendritic cells by T(S) cells: the crucial role of inhibitory receptors ILT3 and ILT4. Nat Immunol 2002;3 :237–43. Colonna M, Samaridis J, Cella M, et al. Human myelomonocytic cells express an inhibitory receptor for classical and nonclassical MHC class I molecules. J Immunol Baltim Md 1950 1998;160 :3096–100. Agaugué S, Carosella ED, Rouas-Freiss N. Role of HLA-G in tumor escape through expansion of myeloid-derived suppressor cells and cytokinic balance in favor of Th2 versus Th1/Th17. Blood 2011;117 :7021–31. He J, Xu J, Yu X et al . Overexpression of ANGPTL2 and LILRB2 as predictive and therapeutic biomarkers for metastasis and prognosis in colorectal cancer. Int J Clin Exp Pathol 2018;11 :2281–94. Jeong S, Park S, Park B-W et al . Human Leukocyte Antigen-G (HLA-G) Polymorphism and Expression in Breast Cancer Patients. Tang J (ed.). PLoS ONE 2014;9:e98284. Iyer AS, Chapoval SP. Neuroimmune Semaphorin 4A in Cancer Angiogenesis and Inflammation: A Promoter or a Suppressor? Int J Mol Sci 2018;20, DOI: 10.3390/ijms20010124. 13. Li D, Wang L, Yu L et al . Ig-like transcript 4 inhibits lipid antigen presentation through direct CD1d interaction. J Immunol Baltim Md 1950 2009;182 :1033–40. Li D, Hong A, Lu Q et al . A novel role of CD1c in regulating CD1d-mediated NKT cell recognition by competitive binding to Ig-like transcript 4. Int Immunol 2012;24 :729–37.